Susceptibility to Phytophthora Cinnamomi of two Grapevine Rootstock Clones after Thermotherapy - Marais, P. G.; Hattingh, M. J. (South African Journal of Enology and Viticulture, 2017)
The grapevine rootstocks 99 Richter clone I/30/1H74 infected with grapevine fleck and leafroll and 99 Richter Prosperi Super subclone 5 infected with stem pitting and leafroll were more susceptible to Phytophthora cinnamomi without treatment than after heat treatment to eliminate viruses. Recent field observations by various local workers (unpublished) and claims by local growers suggested that 99 Richer (Vitis berlandieri P. x V rupestris S.) grapevine rootstock material previously subjected to thermotherapy is more susceptible to Phytophthora cinnamomi Rands than untreated material. This contribution provides data on the effect of thermotherapy on the susceptibility of two 99 Richter rootstock clones to P. cinnamomi.